Electrodeposition of Ternary Zinc-Cobalt-Iron Alloys from a Chloride Bath (A Replacement for Cadmium in Aeronautical Industry) - Z. F. Lodhi; H. A. Terry; J. H. W. De Wit (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Zinc and its alloys have been extensively used as replacements for Cadmium coatings in aeronautical and automobile industries. Zn alloys with low Co or Fe have been highly investigated but coatings with higher amount of Co are very difficult to achieve due to anomalism associated with these coatings. Anomalous Zn-Co-Fe alloy is a relatively recent addition to the family of Zn alloys. It is found that the addition of Fe in the electrolyte assist in overcoming the anomalism. In this research Zn-Co-Fe alloys especially with higher amount of Co (>15%) and Fe (~1%) are investigated, after overcoming the anomalism associated with its deposition, and the corrosion resistance is compared with pure Zn and Cd. It is found that an increase in Co to higher than 25 % accounts for a shift in the OCP to a level near Cd yet keeps it electronegative to steel. The coating shows superior corrosion resistance, in terms of its sacrificial and barrier properties in 3.5% NaC1 as compared to Zn and Cd.